PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM PEMBATALAN PERJANJIAN JUAL BELI AKIBAT PERBUATAN MELAWAN HUKUM (CONTOH KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 523 K/PDT/2017) - Angelica Natalie; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2018)
There are differences between contract and tort laws, which lies in the issue of consent. Because in a contract, the parties need to enter an agreement knowingly and without being coerced for the contract to be valid, that means the parties are aware of the risk entailed and the outcome of the contract. Damages in contract claim usually happened because of mistakes or misunderstandings between the parties. On the other hand, the interaction in a tort is never based on consent. Torts generally involve an intrusion by one party into the privacy, health, profit and safety of the victim. In fact, if the victim consents to the tortious conduct, it can serve as a defense that will prevent them from recovering damages. However in Indonesia court of law, the judges accept to restore damages and even the cancellation of the agreement or contract between the parties due to tort, the judges in many cases have shown that they accepted tort as a reason for cancellation of an agreement, this provides legal protection for the parties in cancellation of the sale and purchase agreement due to tort, even if it’s not ensured that all contract cases can be solved this way or if it’s even lawfully right, as there is an important differences between tort and breach in contract, the case example can be seen on Supreme Court Verdict Number 523 K/PDT/2017 which verdicted undue influence causing a tort and cancelled the sale and purchase agreement between the parties.